Hours Worked of the Self-Employed and Agglomeration - Zhengyu Cai (Global Labor Organization (GLO), 2018)
This paper investigates the causal effects of agglomeration on hours worked by the self-employed. The IV estimations instrument for urbanization and localization using the minimum distance from the work Public Use Microdata Area centroid to the United States' coastlines and estimated industry share in 1930. The 2SLS results demonstrate that urbanization and localization decrease and increase hours worked of the self-employed, respectively. These results are mainly from outsourcing and competition, whereas sorting, simultaneity, and agglomeration wage effect are less likely to be influential. Additionally, only small business owners perceive the pressures of competition in localization economies. The young unincorporated self-employed are more likely to be affected by peer competitors, whereas the elder unincorporated perceive more pressures from large firms.
Keywords: J10; J22; J31; R11; R12; 330; Self-employed; hours worked; urbanization; localization; competition; coastlines